Cost-effectiveness of Oral Regimens for Adolescents With Chronic Hepatitis C Virus Infection. Issue 6 (June 2020) - Zhou, Hua; Lu, Yanming; Wu, Bin; Che, Datian
Abstract : Background: Novel oral regimes have been approved for treating hepatitis C virus (HCV) infection in adolescents due to their superior effectiveness and safety. However, its economic outcome is still unclear in this population. The current analysis investigates the cost-effectiveness of novel oral regimens compared with that of pegylated interferon α with ribavirin (PR) therapies in adolescents in the context of the United States and China. Methods: A Markov model was developed to measure the economic and health outcomes of ledipasvir/sofosbuvir (LS) for genotypes 1 and 4, sofosbuvir/ribavirin (SR) for genotype 2, and ledipasvir/sofosbuvir/ribavirin (LSR) for genotype 3 HCV infection compared with the outcomes of PR treatment. Clinical costs and utility inputs were gathered from published sources. Lifetime discounted quality-adjusted life years (QALYs), costs, and incremental cost-effectiveness ratios (ICERs) were measured. The uncertainty was facilitated by 1-way and probabilistic sensitivity analyses. Results: In the United States, the ICERs of LS strategy were $14, 699 and $14, 946/QALY for genotypes 1 and 4 HCV infection, respectively; the ICER of SR strategy for genotype 2 was $42, 472/QALY; and the ICER of LSR for genotype 3 was $49, 409/QALY in comparison with the PR strategy. In Chinese adolescents, LS for genotypes 1 and 4, SR for genotype 2, and LSR for genotype 3 were the dominant alternatives to the PR strategy. The results were robust to sensitivity analyses. Conclusions: Novel oral regimes for adolescents with HCV infection are likely to be cost-effective in the context of the United States and China. Abstract : Supplemental Digital Content is available in the text.